Revisiting Graduate Student Training to Address Agricultural and Environmental Societal Challenges. Issue 1 (1st October 2017) - Duckworth, Owen W.; Andrews, Megan Y.; Cubeta, Marc A.; Grunden, Amy M.; Ojiambo, Peter S.
Abstract : Core Ideas: Society is faced with daunting environmental and agricultural challenges. There is a pressing need for multidisciplinary teams of collaborative scientists. Novel graduate educational models may be needed to train students to address grand challenges. An example of illustrating the model through microbiome science of plants and soil is presented. Society and the higher education system are faced with daunting challenges associated with supplying food, energy, and water to a growing population while maintaining environmental quality and preserving natural resources. Too often, the higher education system does not facilitate collaborative immersion required to foster concerted multidisciplinary efforts needed to address societal grand challenges. In this commentary, we present an innovative model of cohort education, which equips graduate students with core skills and enables collaborative dissertation research among students. In addition, we provide an example of a program aimed at understanding the plant–soil microbiome, a critical research area that may yield significant advances in plant health and productivity.